NILAI BUDAYA KELUARGA BATAK TOBA DI KELURAHANSAIL TENAYAN RAYA - Amran Sipahutar; Swis Tantoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The aim of this research to find out how to socialiszation the Batak Toba culture values in Batak Toba family in Sail district and what the family measures to legate the Batak Toba culture in family.Data analysis to answer the problems in this research was qualitative with descriptive approach and the analized by theory of this research. Purposive sampling of this research was the informant as 7 people with one coustum chairman, four old sters, and two childs. The result of this research in field the Batak Toba culture values still exist among others the principle of kinship in dalihan na tolu and the life aim of Batak person. The family level of unerstanding of Batak Toba culture values most of the only parents side. While the others fellow of family c’childs only as a matter of fact. To instill and to promulgate the Batak Toba culture values still minim. The result of this research shown that parenting communication patterns, and fellow family members have changed. Most of the family in Sail district used indonesian languange in home. The child interest in learning Batak Toba culture values in Sail district was wear off and the child more like modern things.Keyword: Values, Culture, Family, Batak Toba